Eye movements of beginning and more skilled readers - Sardeira, Marina (2012)
The present study aimed to analyze and compare the eye movements of beginning (2nd grade) and more skilled (4th grade) readers, during reading words and pseudo-words aloud, that differ in frequency (just for words), regularity and length. In this way, one intends to analyze the process of visual information extraction, by both groups, and detect experience and practice-related changes in the ocular behavior. The eye movements of 34 children were monitored, while these were reading words/pseudo-words lists, and this was accomplished using eye-tracking technology. The results show statistically significant differences between the two groups, in mean and total fixations duration for high-frequency words, in mean fixation duration for regular words and in the mean saccade amplitude in irregular pseudo-words. However, no significant differences were found between the groups on the study of the other variables. Nevertheless, the results suggest that skilled readers tend to show more effective eye movements, what determined a lesser effect of words’ frequency, regularity and length on this group. Moreover, the pseudo-words processing was more difficult than that of words, in both groups.